IL-6, IL-17 and Stat3 are required for auto-inflammatory syndrome development in mouse. Issue 1 (December 2018) - Oike, Takatsugu; Kanagawa, Hiroya; Sato, Yuiko; Kobayashi, Tami; Nakatsukasa, Hiroko; Miyamoto, Kana; Nakamura, Satoshi; Kaneko, Yosuke; Kobayashi, Shu; Harato, Kengo; Yoshimura, Akihiko; Iwakura, Yoichiro; et al.
Abstract Auto-inflammatory syndrome, a condition clinically distinct from rheumatoid arthritis, is characterized by systemic inflammation in tissues such as major joints, skin, and internal organs. Autonomous innate-immune activation is thought to promote this inflammation, but underlying pathological mechanisms have not been clarified nor are treatment strategies established. Here, we newly established a mouse model in which IL-1 signaling is conditionally activated in adult mice (hIL-1 cTg) and observed phenotypes similar to those seen in auto-inflammatory syndrome patients. In serum of hIL-1 cTg mice, IL-6 and IL-17 levels significantly increased, and signal transducer and activator of transcription 3 (Stat3) was activated in joints. When we crossed hIL-1 cTg with either IL-6- or IL-17-deficient mice or with Stat3 conditional knockout mice, phenotypes seen in hIL-1 cTg mice were significantly ameliorated. Thus, IL-6, IL-17 and Stat3 all represent potential therapeutic targets for this syndrome.